Somatosensory and motor evoked potentials as biomarkers for post-operative neurological status. Issue 5 (May 2015) - Holdefer, R.N.; MacDonald, D.B.; Skinner, S.A.
Highlights Intraoperative evoked potentials (EPs) are often used during surgery as surrogates for true clinical endpoints. A three step framework recently proposed by the Institute of Medicine was used to evaluate EP biomarkers as surrogate endpoints. Causality guidelines and contingency analysis provided partial validation of EP surrogates.